Sleepwalking in Sexual Abuse Case Report - Güler, Gülen; Yıldırım, Veli; Toros, Fevziye (The Bulletin of Legal Medicine, 2014)
Physical, sexual and emotional abuse in childhood can lead to many other psychiatric disorders. The most common psychiatric disorders after sexual abuse are anxiety disorders, depression, post traumatic stres disorder, eating disorders and sleep disorders. Although almost all psychiatric disorders can affect sleep patterns, triggering sleep walking due to sexual abuse is a rare condition. In this case report, sleepwalking triggered by sexual abuse case will be discussed. Key Words: Sexual abuse; sleepwalking; post traumatic stres disorder